Fine root dynamic characteristics and effect on plantation's carbon sequestration of three Salix shrub plantations in Tibetan Plateau alpine sandy land. Issue 6 (2nd February 2021) - He, Lingxianzi; Jia, Zhiqing; Li, Qingxue; Zhang, Youyan; Wu, Rina; Dai, Jie; Gao, Ya
Abstract: Desertification land in Gonghe Basin of Tibetan Plateau, China accounts for 91.9% of the total land area. Vegetation restoration and reconstruction with desert shrubs in degraded ecosystem are effective ways to prevent and control desertification. However, the evaluation studies of fine root dynamic characteristics of desert shrubs and their contribution to carbon sequestration of plantation are limited. To gain a better understanding of vegetation restoration, the vertical distribution of fine root biomass, fine root decomposition, fine root turnover was investigated, as well as their coupling effect on carbon sequestration of plantation in three desert vegetation. The results estimated that the total decomposition time of fine roots of Salix cheilophila ( S. cheilophila ), Salix psammophila ( S. psammophila ), and Salix microstachya ( S. microstachya ) are 39.00, 27.99 and 35.95 years. Biomass carbon density for three Salix plantations ranged from 1.42 to 2.39 t/hm 2, which showed that three Salix plantations in alpine sandy land are an important carbon pool. In addition, fine root biomass carbon density for the three shrub plantations varied significantly. Fine root biomass carbon density for S. psammophila reached the largest among the three plantations, which was 1.48 t/hm 2, accounting for the ratio of 62% of the plantation total biomass carbon density. The results indicated that the root system of S. psammophila, especially the fine roots, was very developed, which was conducive to soil water transportation and carbon sequestration. Therefore, S. psammophila might be a better species for carbon sequestration of plantation in alpine sandy areas. The carbon input from the fine roots of the three shrub plantations through decomposition and turnover into the plantations accounts for 11.5% to 15.5% of total carbon sequestration of plantations. Therefore, the fine roots dynamics must be considered for long‐term carbon pool estimations in three Salix plantations, otherwise the total carbon sequestration of plantations would be underestimated. Abstract : The total decomposition time of fine roots of Salix cheilophila, Salix psammophila, and Salix microstachya were significantly larger than that of other regions in desert ecosystem. The increase of N concentration in fine roots of Salix would promote the increase of net primary productivity. The contribution of fine roots to carbon storage of plantation could reach 16% through input soil carbon by dynamic activities such as turnover and decomposition.